STRONG CONVERGENCE OF THREE-STEP ITERATIVE PROCESS WITH ERRORS FOR THREE MULTIVALUED MAPPINGS - Eslamian, M.; Homaeipour, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
In this paper, we introduced a three-step iterative process with errors for three multivalued mappings satisfying the condition (C) in uniformly convex Banach spaces and establish strong convergence theorems for the proposed process under some basic boundary conditions. Our results generalized recent known results in the literature.